The influence of the blocker of mineralocorticoid receptors eplerenone on the dynamics of the structural-functional state of the myocardium in patients with non Q-wave myocardial infarction after 3 and 6 months of treatment - V.P. Ivanov (Danylo Halytsky Lviv National Medical University, 2018)
Aim. Assessment of the dynamics of the structural and functional state of the myocardium in patients with non Q-wave myocardial infarction in 3 and 6 months depending on the use of the blocker of the mineralocorticoid receptors eplerenone.